Odontogenic myxofibroma arising in a patient with a past history of carcinoma - Joshna Rani Premara; Anusha Vaddi; Ajay Kumar Enibera; Haritha Kiranmai Balli (Wolters Kluwer Medknow Publications, 2020)
Odontogenic myxofibroma (MF) is a benign odontogenic neoplasm that predominantly occurs in the mandible. It is a variant of odontogenic myxoma. There are several case reports of odontogenic MF reported in the literature. However, none of them were associated with a past history of malignancy. This article presents a case of odontogenic MF in a patient with a past history of treated carcinoma of the breast and rectum.